Purpose and Performance: The Direct Impact of Psychological Well-Being on Academic Outcomes in University Students - Arnas, Riska; Ginanjar, Ani Yanti; Anisah, Ani Siti; Munggaran, Silvi Wulan (Indonesian Scientific Publication, 2025)
Psychological well-being (PWB) is increasingly recognized as a critical determinant of academic success. Despite extensive focus on cognitive and behavioral predictors, the direct role of PWB particularly its multidimensional aspects remains underexplored. This study investigates whether PWB directly predicts academic performance among university students, independent of motivational mediators. A cross-sectional survey was conducted with 365 undergraduate students across various disciplines. Ryff’s 42-item Psychological Well-Being Scale was used to assess PWB, while academic outcomes were measured through self-reported GPA and the Utrecht Work Engagement Scale–Student Version (UWES-S). Data were analyzed using confirmatory factor analysis and multiple regression techniques. Findings indicate that PWB significantly predicts both GPA (β = 0.35, p < .001) and academic engagement (β = 0.40, p < .001). Subdimensions such as purpose in life and self-acceptance emerged as the most influential predictors. The model demonstrated strong construct validity (CFI = 0.94; RMSEA = 0.045). These results suggest that PWB operates as a direct driver of academic outcomes and not merely as a background variable or a mediator via motivation. Psychological well-being is a robust and independent predictor of academic performance. Interventions that enhance purpose in life and self-acceptance could significantly benefit student achievement. These findings advocate integrating well-being into academic support strategies, indicating a shift in how educational success is conceptualized.